Intimate partner violence and help-seeking: The role of femicide news - Marco Colagrossi; Claudio Deiana; Davide Dragone; Andrea Geraci; Ludovica Giua; Elisa Iori (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
Exploiting high-frequency data from the Italian anti-violence helpline and a unique geolocalized dataset on killings of women, we show that the news coverage of a femicide triggers an increase in calls to the helpline. The effect is detectable in the week following the news and in the province where the femicide has occurred. These findings are consistent with a model in which the news of a femicide increase expectations about future intimate partner violence in case no call is made.
Keywords: I18; I38; J12; 330; Gender-based violence; Helpline; Intimate partner violence; Physical violence; Psychological violence; Sexual violence